Penerapan Teknik Color Grading dan Musik Scoring pada Tahap Paska Produksi Film Horor "Waktu Terlarang" - Dian Retno Ariani; Fandy Neta; Ihwan Mansur Munandar (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2021)
Film is one of the modern and effective communication media as sending good information or messages, supporting interesting stories, clear sound, clearimages, and high-resolution video, and the film editing process will greatly help to make films clearer in realizing the purpose of the film to be made. Itsdevelopment is so fast, this happens in all aspects, both in terms of the story to its implementation. Along with the development of the current era, the filmalso experienced a development by having a lot of film genres circulating in the midst of the community, one of which is the genre of horror films that arelifted from a public trust that occurs in the surrounding environment, namely myths. This final project the author makes a short film that lifts the myth of sleepdeprivation at sunset and applies color grading techniques and music scoring as a solution for creating digital video quality. This issue is interesting todiscuss because it will help improve and provide new colors in Indonesian cinema.